Anxiety and Coping Stress Strategies in Researchers During COVID-19 Pandemic - Batista, Patrícia; Afonso, Anabela; Lopes, Manuel; Fonseca, César; Oliveira-Silva, Patrícia; Pereira, Anabela; Pinho, Lara (Frontiers in Public Health, 2022)
The current COVID-19 pandemic has affected the whole world, leading to changes in one's personal and working life. In the most diverse areas, researchers were one of the classes that most had to reinvent themselves. Aim: To assess the anxiety, depression, stress, fears, and coping strategies in Portuguese researchers during the COVID-19 pandemic. Participants and Methods: A total of 243 researchers, average age 37.9  9.6, participated in an online questionnaire. The study was performed between 1st June to 11th August 2021. The questionnaire included a Depression, Anxiety and Stress (DASS-21), Fear of COVID-19 scale (FCV-19S), and Coping Inventory for Stressful Situations (CISS). Results: The findings suggest being female and younger seem to be related to more significant fears. Singles and younger researchers showed higher values of stress, depression, and anxiety. Research areas, such as medical and health sciences, presented higher levels in the DASS-21 depression and stress scale (p<0.05). Also, the results showed a moderate or moderate strong significant positive linear relationship between the scales (p<0.001): DASS-21 stress, DASS-21 anxiety and DASS-21 depression (r>0.70); CISS-21 emotional-oriented with DASS-21 stress (r=0.683), DASS-21 depression (r=0.622), and DASS-21 anxiety (r=0.557); and Emotional fear and Cognitive fear (r=0.652). Conclusion: The findings of this study support the growing concern for the psychological well-being of researchers and the need for intervention with more extensive and diverse studies.